Reunion at the shore - McClain, Lee Tobin (McClain, Lee Tobin. Off season, 2020)
"Ria and Drew Martin's chemistry had always kept their marriage together--until suddenly it didn't. Now a single mom, hotel manager Ria is at a loss when one of her teen daughters starts spiraling. Panicked, she calls on her estranged ex-husband for backup, but she's not prepared for the man he's become--or the unresolved emotions that still linger between them. After his divorce, Drew pulled away from everyone when he lost his eyesight and his job on the police force. Now that he's realized how much his daughters need their dad, Drew is determined to make things up to them. He's less sure where he stands with Ria. They had real reasons for ending their marriage, but they've both changed during their time apart. And being with her again in the place where they first fell in love brings back memories of all that they once had. Can they overcome their past to reunite their family, this time forever?"--Page 4 of cover